Pengaruh Current Ratio dan Debt to Equity Ratio pada Return On Assets RS Pertamedika IHC Tahun 2014-2023 - Handini, Annisa Aprisila; Humaira; Putri Sesa Lestari An; Septi Sartika Sari (Economics and Business Faculty UNUSIA, 2024)
This study aimed to assess the impact of liquidity and solvency ratios on profitability at Pertamedika IHC Hospital between 2014 and 2023. The methodology used was multiple linear regression, using secondary data obtained from the hospital's annual reports. The findings of this study indicated that both current ratio and debt to equity ratio (DER) had a significant positive influence on return on assets (ROA). Together, these two ratios could explained 59% of the variation in hospital profitability. However, this study had several limitations, including limited data coverage and a focus on only two financial ratios. Therefore, it was recommended for future research to expand the scope of the study, include additional variables, and apply more sophisticated analytical methods in order to gain a deeper understanding of the factors affecting hospital financial performance.